The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.780234
|View full text |Cite
|
Sign up to set email alerts
|

“Because I'm Bad at the Game!” A Microanalytic Study of Self Regulated Learning in League of Legends

Abstract: Self-regulated learning (SRL) is a form of learning guided by the student's own meta-cognition, motivation, and strategic action, often in the absence of an educator. The use of SRL processes and skills has been demonstrated across numerous academic and non-academic contexts including athletics. However, manifestation of these processes within esports has not been studied. Similar to traditional athletes, esports players' performance is likely correlated with their ability to engage SRL skills as they train. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Esports mirrors sports and academic domains, in that those with greater self-regulation outperform their peers with less developed self-regulatory skills (Trotter, Coulter, Davis, Poulus, & Polman, 2021, Trotter, Obine, & Sharpe, 2023. Kleinman, Gayle, and Seif El-Nasr (2021) suggests that esports may be an engaging domain to train SRL skills, which could then transfer into other domains such as academia. However, to date, no research has explicitly explored this possibility empirically.…”
Section: From Learning "What" To Learning "How"mentioning
confidence: 99%
“…Esports mirrors sports and academic domains, in that those with greater self-regulation outperform their peers with less developed self-regulatory skills (Trotter, Coulter, Davis, Poulus, & Polman, 2021, Trotter, Obine, & Sharpe, 2023. Kleinman, Gayle, and Seif El-Nasr (2021) suggests that esports may be an engaging domain to train SRL skills, which could then transfer into other domains such as academia. However, to date, no research has explicitly explored this possibility empirically.…”
Section: From Learning "What" To Learning "How"mentioning
confidence: 99%
“…The Miller and Brown (1991) and Zimmerman (2000) models of self-regulation have been previously used to measure selfregulation in esports (Kleinman et al, 2021;Trotter et al, 2021Trotter et al, , 2022. This study has chosen to use the Miller and Brown (1991) model, which includes seven phases of self-regulation (i.e., information input, self-evaluation, instigation to change, search, planning, implementation and plan evaluation) to allow for comparison of this studies results, with quantitative self-regulation results from a previously measured global population of e'athletes (Trotter et al, 2021).…”
Section: Self-regulationmentioning
confidence: 99%
“…Although limited, this evidence suggests that like other sporting domains, self-regulatory skills may play a crucial role in esports performance. Research has also indicated differences in self-regulated learning between experts and novice e’athletes ( Kleinman et al, 2021 ). Specifically, in the preparatory phase, novices were found to prioritize process goals more frequently than experts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In esports, having good meta-cognition means that one could plan, analyze and set goals for in-game performance improvements (Kleinman et al, 2021), identify how and why a mistake was made and find the right way to fix it (Himmelstein et al, 2017), make sense of the performance data to engage in self-tracking and -reflecting behaviors (Rapp, 2018), and search for external resources to develop retainable knowledge (Golub, 2010). Certain game designs facilitate such skills.…”
Section: Rubric Of Competenciesmentioning
confidence: 99%